Smart Signage with Augmented Reality: Inclusive Coworking - Arias-Flores, Hugo (2024)
This project focuses on the implementation of augmented reality signage designed to enhance user experience in a coworking space. The signage integrates 2D animations and virtual tours to provide an intuitive and immersive experience, from entry to the desired destination within the establishment. At the main entrance, a totem with a coworking directory features a QR code that visitors can scan to access an interactive directory. The 2D animations, thoughtfully designed with an inclusive approach, utilize validated corporate colors to ensure accessibility, especially for individuals with color vision deficiencies. Each business in the coworking space is identified by a unique corporate color, and internal business floor plans use analogous colors, adjusted to maintain aesthetic coherence and accessibility. In addition to being an effective navigation tool, these animations reinforce the visual identity of the coworking space. Each business within the establishment has an interactive virtual tour that guides visitors from entry to their final destination, providing real-time visual information for effective orientation. The signage system is based on WordPress to offer a seamless and efficient experience without the need to download a specific application. Upon scanning the QR code, users are redirected to a mobile-optimized web page. This page not only provides access to the 2D animations and virtual tours but also offers useful information such as business hours, links to the businesses’ and coworking space's social media, and other relevant details for the visit. This augmented reality signage approach not only enhances the functionality of the space but also ensures that all visitors, regardless of their needs, enjoy an inclusive and efficient experience in the coworking space.